O que faz um núcleo de inclusão e acessibilidade? – contribuições da psicologia escolar para a educação superior - Leite, Anna Paula Martins (2024)
The inclusion and accessibility of students in Higher Education have received greater attention from institutions at this level of education. The INCLUIR Program – Accessibility in Higher Education, created by the Ministry of Education in 2005, has as its main objective to promote the creation and implementation of Accessibility Centers in Higher Education Institutions. However, the Program Guidance Document does not provide specific guidance regarding the minimum team, the training of professionals who must make up the team, nor the location of the accessibility center in the institution's organizational chart, among other gaps. Thus, this research had the main objective of identifying policies, regulations and actions for the inclusion of people with disabilities carried out by Inclusion and Accessibility Centers of Federal Higher Education Institutions in Minas Gerais. The specific objectives were to survey the main projects and services carried out by the Inclusion and Accessibility Centers to guarantee the permanence and completion of courses for students with disabilities and to identify the composition and formation of the teams that work in these Centers and how to provides the role of the School Psychologist for the inclusion of people with disabilities in Higher Education. The study, of a qualitative nature, was carried out through a survey on the websites of the Inclusion and Accessibility Centers of the 11 Federal Higher Education Institutions (IFES) in the State of Minas Gerais to compile information relating to the respective sector, such as name, location in the IFES organizational chart, team, services offered, types of service, projects and actions developed, IFES policies and regulations for Inclusive Education and other information. The empirical material was analyzed through content analysis and organized into the following axes of analysis: 1 – What the Centers offer to students with disabilities and 2 – Training and Composition of the team and where the School Psychologist is ?. We found that the monitoring service was the one that stood out the most in terms of service to students and with regard to the team, we highlight the importance of greater training in the area of inclusive education and the presence of a School Psychologist and Educational. Most IFES in Minas Gerais are committed to the inclusion of students with disabilities and are committed to offering services and projects to guarantee their accessibility and, consequently, their inclusion. However, there are still many challenges to be faced, such as the composition of a multidisciplinary team in the NA with the presence of a psychologist, with employees trained to work with inclusion, the continuous carrying out of teacher training and the effective monitoring of monitors, in addition to keeping websites updated and accessible.